The Work of Cultural Transition: An Emerging Model - Ryba, Tatiana V.; Stambulova, Natalia B.; Ronkainen, Noora J. (Frontiers in Psychology, 2016)
In today’s uncertain, fluid job market, transnational mobility has intensified. Though the concept of cultural transition is increasingly used in sport and career research, insight into the processes of how individuals produce their own development through work and relationships in shifting cultural patterns of meaning remains limited. The transnational industry of sports, in which athletes’ psychological adjustment to cultural transitions has implications for both performance and meaningful life, serves as a backdrop for this article. This study applied the life story method to interviews with 15 professional and semi-professional athletes, focusing particularly on the cultural transition aspect of their transnational athletic careers. The aims of the study were to identify the developmental tasks of cultural transitions and strategies/mechanisms through which cultural transitions were enacted. Three underlying mechanisms of the transition process that assisted athletic career adaptability were social repositioning, negotiation of cultural practices, and meaning reconstruction. Based on the data analyses, a temporal model of cultural transition is proposed. The results of this research provide professionals working in the fields of career counseling and migrant support with a content framework for enhancing migrant workers’ adaptabilities and psychological wellbeing.